Long-term outcomes of surgical radiofrequency ablation for atrial fibrillation in 3 groups of patients - Maly, Jiri; Kautzner, Josef; Krausova, Renata; Rokosny, Slavomir; Netuka, Ivan; Szarszoi, Ondrej; Skalsky, Ivo; Pirk, Jan (The heart surgery forum, 2008)
BACKGROUND: Left atrial surgical radiofrequency ablation represents an applicable and technically less demanding method for treating paroxysmal or permanent atrial fibrillation (AF) as a concomitant procedure. The aim of this study was to review the long-term outcomes of radiofrequency linear ablation for the treatment of AF limited to the left atrium in 3 groups of patients undergoing cardiac surgery. METHODS: The study population consisted of 357 consecutive patients, who were divided into 3 groups on the basis of the underlying disease: group I, 126 patients with nonischemic mitral valve disease; group II, 164 patients with coronary artery disease and aortic and/or ischemic mitral valve disease or who underwent other concomitant procedures; and group III, 67 patients with coronary artery disease only. RESULTS: Follow-up times were between 6 and 48 months (mean, 28.3 + 9.4 months). The 30-day hospital mortality rate was 2.80% (10 patients). Total mortality during the follow-up period reached 4.48% (16 patients). At discharge, 66% of group I patients, 64% of group II patients, and 69% of group in patients were in sinus rhythm. After 24 months, 60% of group I patients, 75% of group II patients, and 67% of group III patients were in sinus rhythm. A subgroup analysis of the patients with permanent AF showed that only 54% of these patients in group I, 52% in group II, and 67% in group III had a restored sinus rhythm at 24 months. Subgroup analysis also revealed that only 6 (27%) of 22 patients with a left atrium diameter >60 mm maintained a sinus rhythm during long-term follow-up. Biatrial contraction was restored in 75% of the patients with a stable sinus rhythm after 6 months of follow-up. Seven patients (2%) with symptomatic postoperative recurrent atrial arrhythmias underwent subsequent catheter ablation. CONCLUSION: Left atrial surgical radiofrequency ablation represents an applicable and technically less demanding method for treating paroxysmal or permanent AF as a concomitant procedure. Our results demonstrate the feasibility of this procedure for paroxysmal and persistent AF, with minimal risks to the patient. For permanent AF, further investigation and extensive intervention are essential.
Keywords: longitudinální studie; Prevalence; komorbidita; nemoci koronárních tepen; Česká republika; výsledek terapie; katetrizační ablace; mužské pohlaví; prevalence; Czech Republic; Coronary Artery Disease; Catheter Ablation; ženské pohlaví; Humans; Comorbidity; fibrilace síní; Heart Valve Diseases; Longitudinal Studies; nemoci srdečních chlopní; Female; Atrial Fibrillation; Treatment Outcome; lidé; Male